Effectiveness of team based learning to teach pharmacology for phase-II MBBS students - N.K. Hashilkar; M.H. Gelula (Al Ameen Medical College, 2014)
Background: TBL (Team based Learning) instructional methods foster applying knowledge in a highly interactive setting. Furthermore, in contrast to PBL (Problem Based Learning), it is a teacher directed method that encourages student- student interaction. Objective: The present study is aimed to assess the effectiveness of TBL over the current conventional tutorial type of teaching-learning strategy. Materials and Methods: The present study was conducted in the department of pharmacology of KLE University's J N Medical College, Belgaum for phase II MBBS students. Students were randomly assigned to either team based learning (TBL) or conventional tutorial (CT) groups. Teaching learning sessions were conducted on similar topics of cardiovascular system following mechanics of TBL or tutorials respectfully. Effectiveness of each session was assessed by common pre-test and post test while, the overall performance was assessed at the end by a common test for both groups. The scores of the two groups were analysed using students t-test. A feedback was obtained from the students regarding their experience with TBL. Results: There was a significant difference between the pre-CT and pre-TBL scores for Anti-hypertensives (p ≤ 0.0001) and congestive cardiac failure (p ≤0.0002) sessions while these scores were not significantly different for Anti-anginals and Renin angiotensin system. However, the comparison of post-CT and post-TBL scores were significantly different (p< 0.05) for each of the four sessions. The scores of the end of the module test showed significant difference (p <0.0001) between the two group. Most of the students appreciated the mechanics of TBL and were satisfied with it. Conclusions: The performance of the students of the TBL group improved in individual sessions as well as the entire module as opposed to the CT group.